Botgo (FAS Sdn. Bhd) / Muhammad Aiman Kamarudin ... [et al.] - Muhammad Aiman, Kamarudin; Muhammad Faris Hakimi, Mohd Rizaini; Nur Afrina binti Mohd, Kamalrulzaman; Nur lzzah Farhana, Zakaria; Siti Zubaidah, Wahab (2019)
This business is based on partnership where it consists of five members which hold important positions in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Fiancial Manager. The business capital is amounted to RM250,000 where the total contribution of each member is RM 50,000 and the rest RM 50,000 is from Bank Islam's loan. BOTGO is one of the most popular bahulu at our company. FAS Sdn Bhd is located near Seri lskandar with address; Lot 3152, Jalan Teknologi 2, Seri lskandar, Bota, Perak. FAS Sdn Bhd is a company which focuses on food production in Malaysia. Bahulu is one of malay traditional cake that has differences in size and shape that makes this cake looks interesting and suitable to serve for any occasion. The light and dry texture gives an opportunity to this cake to be one of marketable product as people love simple things especially food. Moreover, the simple steps and ingredients give a lot of benefit to our company and we are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting, we decided to make some innovation by implying our creativity and modern element in this bahulu making. Nowadays, people love to experiment with their food. Therefore, we choose to create this product which people can bake their own bahulu with instant bater which will help them bake faster. So, with our product, it will bring advantages to people who wants to start baking, career women who do not have a lot of time to prepare food and other people too. We will expect that our business will become more developed in the near future because with the new innovation in our bahulu, the demand will increase not only during any occasion but it might be a new daily snack. Bahulu production has the potential of being a profitable business if it is done in modern way with large scale and systematically managed. This will give more advantages for us to make our product more profitable and stable in the long run.